Difusi Sistem E-SPMI di Institut Agama Islam Negeri (IAIN) Kudus; Analisis Model Rogers (QUALITY, 2023)
Diffusion of E-SPMI System at State Islamic Institute (IAIN) of Kudus; Analysis of Rogers Model. This article discusses the diffusion process of the E-SPMI system at IAIN Kudus. The E-SPMI system was put in place with the aim of improving the quality assurance system, especially in the implementation of the PPEPP cycle. The purpose of this study is to find out how the diffusion process of the E-SPMI system and what factors influence it. The results show that the diffusion process goes through several stages, starting from the knowledge stage, which encourages institutions to develop E-SPMI because of the need for innovation and efficiency in quality assurance. Furthermore, the persuasion stage involves socializing the concept and advantages of E-SPMI to related parties and stakeholders. The great advantages and efficient costs of E-SPMI encourage a collective decision to adopt it. Implementation begins with E-SPMI data filled by study programs and supervised by LPM. Although the results of implementation could not yet be measured during the confirmation phase, leadership support and positive user perceptions point to a bright future. Factors that influence the technology diffusion process in higher education environments. Factors such as perspective, data complexity, and data integration in the SMURT system affect the diffusion process of E-SPMI.Artikel ini membahas proses difusi sistem E-SPMI di IAIN Kudus. Sistem E-SPMI diberlakukan dengan tujuan untuk meningkatkan sistem penjaminan mutu khususnya dalam pelaksanaan siklus PPEPP. Tujuan pengkajian ini adalah untuk mengetahui bagaimana proses difusi sistem E-SPMI dan faktor apa sea yang mempengaruhinya. Hasil penelitian menunjukkan bahwa proses difusi melewati beberapa tahap, dimulai dari tahap pengetahuan, yang mendorong institusi untuk mengembangkan E-SPMI karena kebutuhan akan inovasi dan efisiensi dalam penjaminan kualitas. Selanjutnya, tahap persuasi melibatkan sosialisasi konsep dan keunggulan E-SPMI kepada pihak terkait dan pemangku kepentingan. Keunggulan besar dan biaya efisien E-SPMI mendorong keputusan kolektif untuk mengadopsinya. Implementasi dimulai dengan pengisian data E-SPMI oleh program studi dan diawasi oleh LPM. Meskipun hasil implementasi belum dapat diukur selama fase konfirmasi, dukungan pimpinan dan persepsi positif pengguna menunjukkan masa depan yang cerah. Faktor-faktor yang mempengaruhi proses difusi teknologi di lingkungan pendidikan tinggi. Faktor-faktor seperti perspektif, kompleksitas data, dan integrasi data dalam sistem SMURT mempengaruhi proses difusi E-SPMI.